Out of the reservoir: Phenotypic and genotypic characterization of a novel cowpox virus isolated from a common vole - Hoffmann, Donata; Franke, A.; Jenckel, Maria; Tamošiūnaitė, A.; Schluckebier, Julia; Granzow, Harald; Hoffmann, Bernd; Fischer, Stefan; Ulrich, Rainer; Höper, Dirk; Goller, Katja; Osterrieder, N.; et al. (Journal of Virology, 2015)
The incidence of human cowpox virus (CPXV) infections has increased significantly in recent years. Serological surveys have suggested wild rodents as the main CPXV-reservoir. We characterized a CPXV isolated during a large scale screening from a feral common vole. A comparison of the full-length DNA-sequence of this CPXV-strain with a highly virulent pet rat CPXV-isolate showed a sequence identity of 96%, including a large additional ORF of about 6,000 nucleotides, which is absent in the reference CPXV-strain Brighton Red. Electron microscopy analysis demonstrated that the vole isolate, in contrast to the rat strain, forms A-type inclusion bodies (ATI) with incorporated virions, consistent with the presence of complete ati and p4c genes. Experimental infections showed that the vole CPXV-strain caused only mild clinical symptoms in its natural host, while all rats developed severe respiratory symptoms followed by a systemic rash. In contrast, common voles infected with a high dose of the rat CPXV showed severe signs of respiratory disease but no skin lesions, whereas infection with a low dose led to virus excretion with only mild clinical signs. We concluded that the common vole is susceptible to infection with different CPXV-strains. The spectrum ranges from well-adapted viruses causing limited clinical symptoms to highly virulent strains causing severe respiratory symptoms. In addition, the low pathogenicity of the vole isolate in its eponymous host suggests a role of common voles as a major CPXV reservoir, and future research will focus on the correlation between viral genotype and phenotype/pathotype in accidental and reservoir species.